A comparative study of the effect of constant and environmental tenperatures in the biomass production from the microbiota of kefir grain - Arévalo Ortiz, Fermín (2007)
In this comparative study the effect of the temperature was evaluated in the fermentation and production of biomass coming from the microbiote of the grain of kéfir using whole milk as sustrate. Inocule was used at 5% of concentration and it was allowed to ferment for 4 cyc1es of fermentation at reason of 24 hours per cyc1e for being the results evaluated later at two given temperatures: constant at 24 ºC and variable, between 19 and 26 ºc. The evaluation revealed that there was not a significant difference between constant and variable temperatures of fermentation concerning to the weight, that is to say concerning to the yield in biomass, although there was a difference respect to grains of kéfir consistency. The results demonstrated that the grains of kéfir obtained at variable temperature of fermenta non, it means at ambient temperature between 19 and 26 ºC, they turned out to have bigger consistency than grains fermented at constant temperature of 24 ºc. Finally, this study demonstrated that at least in our country, Peru, in places where c1imates do not present extreme temperatures, the fermentation of grains of kéfir with the purpose of producing Kefir and biomass at ambient temperature, is viable and of great importance, since it can be carried out without spending additional energy in the process.